Atmosphere-Space Interactions Monitor (ASIM): State of the Art - Pere Blay; Lola Sabau-Graziati; Víctor Reglero; Paul H. Connell; Juana M. Rodrigo; Juan M. Macian Macián; José T. Biosca; Chris Eyles (Acta Polytechnica CTU Proceedings)
Atmosphere-Space Interactions Monitor (ASIM) mission is an ESA pay load which will be installed in the Columbus module of the International Space Station (ISS). ASIM is optimized to the observation and monitoring of luminescent phenomena in the upper atmosphere, the so called Transient Luminous Event (TLEs) and Terrestrial Gamma Ray Flashes(TGFs). Both TLEs and TGFs have been discovered recently (past two decades) and opened a new field of research in high energetic phenomena in the atmosphere. We will review the capabilities of ASIM and how it will help researchers to gain deeper knowledge of TGFs, TLEs, their inter-relationship and how they are linked to severe thunderstorms and the phenomena of lightning.